(untitled) (Economic Journal of Nepal, 2017)
The study examines the dynamic relationship along with disputes between the trade of China and the United States of America (U.S.A.). The study used a comparative analysis by investigating relative changes in the position of the foreign trade since 1960 A.D. On the basis of more than 50 years observations, there is a significant relationship between foreign trade of China and the U.S.A. Similarly, there are different causes of trade disputes between china and the U.S.A.. Its comparative advantage is that it can produce goods for lower costs than other countries. So, recent days, American companies cannot compete with low costs of China. Another reason is the view of President Donald J Trump like ’the trade wars good and easy to win’. In short run, trade wars have a positive impact on trade, but in the long term, it makes slow rate of economic growth, employment and weak the protected domestic industry. Similarly, it affects both economies of China and the U.S.A. and also promotes regional trade and dumping policy. Accordingly, exports base of Nepal is weak and its exports to China are being affected due to trade wars, despite the fact that trade to the United States does not affect.